2023
DOI: 10.3390/ani13040761
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Luteolin against Pseudorabies Virus In Vitro and In Vivo

Abstract: Pseudorabies virus (PRV) can cause acute swine disease leading to economic losses worldwide and is a potential causative agent of viral encephalitis in humans. Although effective vaccines are available, an increasing number of variants have emerged in China, and identifying effective antiviral agents against PRV to prevent latent infection is essential. In this study, we assessed the antiviral activity of luteolin against PRV in vitro and in vivo. Luteolin was found to significantly inhibit PRV at a noncytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Studies assessing a synergistic effect when the compounds are administered in combination with current monoclonal treatments are also desirable. In addition, we have evidenced luteolin to target combinations of VP35IID, NtPKR or PACT heterodimers, offering further mechanistic explanations to its previously reported antiviral effect [40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 61%
“…Studies assessing a synergistic effect when the compounds are administered in combination with current monoclonal treatments are also desirable. In addition, we have evidenced luteolin to target combinations of VP35IID, NtPKR or PACT heterodimers, offering further mechanistic explanations to its previously reported antiviral effect [40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 61%
“…Quercetin can interact with the gD protein, which plays an important role in the virucidal properties of quercetin and inhibition of PRV infection [ 13 ]. Luteolin can inhibit PRV proliferation and cell–cell transmission by inhibiting the expression of the gB gene and protein [ 14 ]. This study found that emodin can also inhibit the expression of the gD and gB genes, block the synthesis of the PRV gB protein and gD protein, and inhibit virus proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It can inhibit the replication of PRV in PK-15 cells by inhibiting gB gene and protein expression and by alleviating virus-induced apoptosis. Moreover, it can play a protective role in PRV-infected mice by delaying symptom onset time, improving survival rate, reducing viral load in tissues and organs, and improving the inflammatory response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[147][148][149] HO-1 exerts antiviral effects against HSV2, bovine viral diarrhea virus, porcine reproductive (virus), and respiratory syndrome virus in vitro. [150][151][152] Men et al 153 proposed that luteolin effectively inhibits PRV replication by inhibiting the expression of viral mRNA and gB protein.…”
Section: Dna Virusesmentioning
confidence: 99%